PERHITUNGAN HARGA POKOK PRODUKSI KERIPIK BAYAM DENGAN METODE FULL COSTING (Studi Kasus Industri Rumah Tangga Keripik Bayam di Kelurahan Mugirejo Kecamatan Sungai Pinang Kota Samarinda) (The Calculation of Production Basic Price of Spinach Chips By Full Costing Method (Case Study at Household Industry of Spinach Chips in Mugirejo Urban Village Sungai Pinang Subcity Samarinda City)) - DINA LESMANA; ANGGUN SAPUTRI (Universitas Mulawarman (University of Mulawarman), 2019)
The high added value is obtained by agro-industry entrepreneurs increase competition. An effort has made to increase profit is processing spinach into spinach chips. The purpose of this study was to calculate the production basic price. Research was conducted from August to October 2018 in the home industry spinach chips in Mugirejo Urban Village, Sungai Pinang Subcity, Samarinda City. The data collected was primary and secondary data. Method of data analysis used the full costing method. The result of the study showed that the production costs incurred by home industry of the spinach chips monthly including raw material costs of IDR1,511,000.00; direct labor costs of IDR2,500,000.00; variable cost of factory overhead of IDR755,000.00; and fixed cost of factory overhead of IDR306.583,33. The calculation result of basic price monthly in household industry of spinach chips is IDR5,072,583.33. The monthly sales is IDR16,500,000.00 and the monthly profit obtained by the household industry of spinach chips is IDR11,427,416.67.